MANAGEMENT OF INSOMNIA USING PHARMOCOLOGY OR NON- PHARMACOLOGY - Muammar Ghaddafi (Universitas Udayana, 2013)
Insomnia is a symptom rather than a diagnosis that may lead to irritability, dissatisfaction and decrease individual productivity. Insomnia can be divided into primary and secondary symptom which cause by other condition, but the mechanism on how this happened still unclear. In addition, relation between insomnia and other clinical problem is always undefined because it is impossible to find out the relation between causes and consequences of this symptom. Practitioner can choose either pharmacotherapy or non-pharmacotherapy in management of insomnia patient. Side effects and efficacy of pharmacotherapy must be considered before we prescribe a medicine to de patient. We also can Choose non-pharmacotherapy which is without side effects, but can be same effective as pharmacotherapy and even more.